Energy propagation modeling of nonlinear soft tissue deformation for surgical simulation. (January 2018) - Zhang, Jinao; Zhong, Yongmin; Smith, Julian; Gu, Chengfan
Realistic modeling of nonlinear soft tissue deformation in real-time is a challenging research topic in surgical simulation. This article presents an energy propagation method based on Poisson propagation for modeling of nonlinear soft tissue deformation for surgical simulation. It carries out soft tissue deformation from the viewpoint of potential energy propagation, in which the mechanical load of an external force applied to soft tissues is considered as the equivalent potential energy, according to the law of conservation of energy, and is further propagated in the volume of soft tissues based on the principle of Poisson energy propagation. The proposed method combines Poisson propagation of mechanical load and non-rigid mechanics of motion to govern the dynamics of soft tissue deformation. Computer simulation results demonstrate that the proposed method is not only able to handle homogeneous, anisotropic, and heterogeneous materials, but also able to accommodate nonlinear deformation of soft tissues.